The Urgency of Criminalizing Stalking and Its Offense Formulation - M. Syamsudin; Sukardi; Huzaimah Al-Anshori; Grees Selly (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
In the digital age, issues related to privacy invasion, repetitive monitoring, and harassment have become increasingly prevalent. One of the most concerning manifestations of these issues is stalking, a pattern of persistent, unwanted behavior that leaves victims feeling threatened, disturbed, and emotionally distressed. As technology advances, opportunities for stalking have expanded, particularly through digital platforms, which enable stalkers to monitor, contact, and manipulate victims more easily than ever before. Unfortunately, in Indonesia, there is a significant gap in the legal framework to address stalking effectively, as existing criminal laws do not yet include specific provisions for such actions. This study examines stalking from legal, social, and psychological perspectives to explore how criminalizing stalking could offer much-needed protection for victims. By adopting a juridical-normative approach, the research reviews relevant laws, regulations, and existing literature to analyze how Indonesia's legal system can adapt to manage stalking incidents better. Findings reveal that stalking profoundly impacts victims, threatening their safety, mental health, and personal freedom. The research underscores the necessity for Indonesia to establish precise legal definitions and clear criteria to classify behaviors as stalking. A well-formulated legal provision addressing stalking would not only provide clarity on the actions that constitute stalking but also outline suitable penalties to deter offenders. Such regulation could serve as a powerful tool to protect victims’ rights and ensure that they are safeguarded against persistent harassment. In conclusion, the study advocates for a comprehensive draft offense formulation on stalking within Indonesia’s criminal law framework to ensure that victims receive the legal protection they need and that perpetrators are held accountable for their actions,